Quantitative evaluation of intracellular sense: antisense RNA hybrid duplexes. - Wang, S (1993)
Previous studies have demonstrated that for an antisense RNA to be effective in attenuating gene expression, a large but indeterminate excess of antisense RNA is required. To quantitatively evaluate RNA hybrid duplex formation, expression vectors containing antisense dihydrofolate reductase (DHFR) cDNAs were transfected into KB and KB-1BT (a DHFR overexpressing variant) cells and transfectants expressing antisense transcripts of exon 1 through intron I (ex1-I) or exons 1 through 4 (ex1-4) were analyzed for hybrid duplex formation. Stable duplexes were detectable in KB-1BT but not in KB cells. Approximately 5-9% of antisense ex1-I RNA and 20-37% of antisense ex1-4 RNA were found in duplexes. The amount of each hybrid duplex RNA was found to be a linear function of intracellular single-stranded antisense RNA levels and a hybrid index, Hs:as, was devised to describe this relationship. Based upon the value of Hs:as for each antisense RNA:mRNA duplex, it is calculated that an approximate 2,800- and 600-fold excess of ex1-I and ex1-4 antisense RNA are respectively required for 50% of DHFR mRNA to be present in duplexes. Results support the hypothesis that intracellular sense:antisense RNA hybrid duplex formation is inefficient and dependent upon the levels, lengths and possibly the structures of the RNAs involved.